PENGARUH KOMITMEN ORGANISASIONAL, STRESS KERJA, KEPUASAN KERJA TERHADAP KINERJA KARYAWAN - Wahyu Imam Buchori; Abdul Qodir Djaelani (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
ABSTRACTThe aim of this research is to know the influence of OrganizationalCommitment, work stress and work satisfaction toward employee’s performance.This research is to do for employees in PT. King Stone Malang. This sample ofthis research more about 60 responders. The method of this research usequantitative data as questioner. The method of the data use interval data in orderto can be analyze the influence by using double linier regression.The result of this research to indicate that the average value answer ofresponders are about Organizational Commitment have better. The average valueof work stress is better that the work stress for employees are not higher. Theaverage value of work satisfaction is better too, but still less maximal. Theaverage value of employee’s performance has been better. From this research theresearcher know that Organizational Commitment has influence that significanttoward employee’s performance, work stress has not influence significant towardemployee’s performance. Work satisfaction has not influence that is notsignificant toward employee’s performance.Keywords : Organizational Commitment, Work Stress, Work satisfaction, andEmployee’s Performance